Microplastic Pollution in Nearshore Sediment from the Bohai Sea Coastline - Zhu, Xiaopeng; Ran, Wen; Teng, Jia; Zhang, Chen; Zhang, Wenjing; Hou, Chaowei; Zhao, Jianmin; Qi, Xutong; Wang, Qing (Bulletin of environmental contamination and toxicology, 2021)
Microplastics are recognized as an emerging global issue in marine environments. In this study, microplastic pollution in subtidal sediments from nine typical stations in the Bohai Sea was investigated. The mean concentration was 458.6 ± 150.0 items/kg of dry weight, varying from 280.0 to 773.4 items/kg. All of the microplastics were categorized according to shape, color and size. Among these microplastics, fiber (77.1%), white/blue/black (85.0%) and small microplastics (< 1500 μm) (82.9%) were the most abundant types. Seven polymer types were identified and were, in decreasing order of abundance, rayon > PE > PS > PP > PET > ABS > PA. The microplastics abundance was of the same order of magnitude as that of other similar areas. The microplastic characteristics suggest that tourism, maritime activities and sewage discharge are possible sources. Our results provide useful information for performing an environmental risk assessment of microplastic pollution in this area.